A Metagenomic Analysis of Mosquito Virome Collected From Different Animal Farms at Yunnan–Myanmar Border of China - Hameed, Muddassar; Wahaab, Abdul; Shan, Tongling; Wang, Xin; Khan, Sawar; Di, Di; Xiqian, Liu; Zhang, Jun-Jie; Anwar, Muhammad Naveed; Nawaz, Mohsin; Li, Beibei; Liu, Ke; et al. (Frontiers in Microbiology, 2021)
Metagenomic analysis of mosquito-borne and mosquito specific viruses is useful to understand the viral diversity and for the surveillance of pathogens of medical and veterinary importance. Yunnan province is located at the southwest of China and has rich abundance of mosquitoes. Arbovirus surveillance is not conducted regularly in this province particularly at animal farms which have public health as well as veterinary importance. Here, we have analyzed 10 pools of mosquitoes belonging to Culex tritaeniorhyncus, Aedes aegypti, Anopheles sinensis, and Armigeres subalbatus species, collected from different animal farms located at Yunnan province of China by using metagenomic next generation sequencing technique. The generated viral metagenomic data reveals that the viral community matched by the reads was highly diverse and varied in abundance among animal farms, which contained more than 19 viral taxonomic families, specific to vertebrates, invertebrates, fungi, plants, protozoa, and bacteria. Additionally, a large number of viral reads were related to viruses that are non-classified. The viral reads related to animal viruses included parvoviruses, anelloviruses, circoviruses, flaviviruses, rhabdoviruses, and seadornaviruses, which might be taken by mosquitoes from viremic animal hosts during blood feeding. Notably, the presence of viral reads matched with Japanese encephalitis virus, Getah virus and porcine parvo viruses in mosquitoes collected from different geographic sites suggested a potential circulation of these viruses in their vertebrate hosts. Overall, this study provides a comprehensive knowledge of diverse viral populations present at animal farms of Yunnan province of China, which might be a potential source of diseases for humans and domestic animals.